El Excentrico, 1959-06-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 20, 1959 [20 de junio de 1959]. Ano 9, No. 20. Cover contains a two photos that were taken at a graduation ceremony at Abraham Lincoln High School.